Mass Flowering of Montane Bamboos in Himachal Praoesh : Ushering in the New Millenium - Goraya, G. S.; Jishtu, Vaneet; Kapoor, K. S.; Pal, Mohinder (Indian Forester, 2003)
Montane bamboos are represented in the western-Himalayan State of Himachal Pradesh by two species i.e. Arundinaria falcata and Arundinaria spathiflora. Both these species, having great ecological and local socio-economic significance, have gregariously flowered across the State during the year 2000 and 2001 respectively. This paper documents specie-wise extent of flowering of these bamboo species in the Sutlej catchment of the State.